Analysis Comparative of Chinese and Indonesia Pronouns - Yi Ying (Humaniora, 2011)
Personal pronouns in communication plays a significant role. Proper use of personal pronouns, communication can proceed smoothly. Misuse of personal pronouns, or failure of communication will be blocked, or even make the communication between two sides break up. Therefore, understanding the language of the two personal pronouns is very important. This study analyzes the Chinese and India and usage of the classification of personal pronouns. Conclusion of the study hope to promote cross-cultural language communication, in particular, help to learn Chinese or learn Bahasa Indonesia in different occasions to use the correct pronouns. The results: (1) Chinese and Bahasa first person pronoun "I" have in common is in the sentence can be a subject and attribute; (2) Bahasa first person pronoun "aku" can not be used in some situations such as: official occasions, and older than themselves, respect for people or strangers or people who speak; (3) Chinese third-person plural pronouns, written language, "they" said that men and women is not the same guy, same use of Bahasa Indonesia kami; (4) Bahasa Indonesia are changes in the form of personal pronouns, while the Chinese personal pronouns do not; (5) the third person pronoun to differentiate between Chinese men and women, and things, but Bahasa Indonesia is no difference between the third person pronoun gender and things; (6) Bahasa Indonesia the personal pronoun is not gender distinction.